Bank interest rate pass-through in the euro area: a cross country comparison - Christoffer Kok Sørensen; Thomas Werner (European Central Bank (ECB), 2006)
The present paper investigates the pass-through between market interest rates and bank interest rates in the euro area. Compared to the large interest rate pass-through literature the paper mainly improves upon two points. First, a novel data set, partially based on new harmonised ECB bank interest rate statistics is used. Moreover, the market rates are selected in a way to match the maturities of bank and market rates using information provided by the new statistics. Secondly, new panel-econometric methods are applied to test for heterogeneity in the pass-through process. The paper shows a large heterogeneity in the pass-through of market rates to bank rates between euro area countries and finally possible explanations of the heterogeneity are discussed.
Keywords: E43; G21; 330; Euro area countries; Interest rate pass-through; Panel Cointegration; Zinsstruktur; Geldpolitik; Zinspolitik; Geldpolitische Transmission; Eurozone; EU-Staaten